2020
DOI: 10.3390/s20030948
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Self-tuning Tracking Differentiator for Motion Measurement Sensors and Application in Wide-Bandwidth High-accuracy Servo Control

Abstract: Sensor differential signals are widely used in many systems. The tracking differentiator (TD) is an effective method to obtain signal differentials. Differential calculation is noise-sensitive. There is the characteristics of low-pass filter (LPF) in the TD to suppress the noise, but phase lag is introduced. For LPF, fixed filtering parameters cannot achieve both noise suppression and phase compensation lag compensation. We propose a fuzzy self-tuning tracking differentiator (FSTD) capable of adaptively adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…It can be concluded that the velocity loop bandwidth is related to the load inertia rate, encoder accuracy, speed controller gain, velocity estimation algorithm, and so on, based on theoretical and experimental analysis. 29 The load inertia rate should be controlled at about 1 when selecting the motor. Too high a load inertia rate limits physical bandwidth, causing significantly increased loss of the guide bar during acceleration and deceleration.…”
Section: Optimization Of Velocity Loop Bandwidthmentioning
confidence: 99%
“…It can be concluded that the velocity loop bandwidth is related to the load inertia rate, encoder accuracy, speed controller gain, velocity estimation algorithm, and so on, based on theoretical and experimental analysis. 29 The load inertia rate should be controlled at about 1 when selecting the motor. Too high a load inertia rate limits physical bandwidth, causing significantly increased loss of the guide bar during acceleration and deceleration.…”
Section: Optimization Of Velocity Loop Bandwidthmentioning
confidence: 99%
“…By substituting the relationships described in Equation (18) into Equations (16) and (17) and neglecting the gyroscopic effects of the quadrotor, the system can be expressed as follows:…”
Section: Backstepping Controlmentioning
confidence: 99%
“…Quadrotors have very simple mechanics since the control of their position is determined by the changes in speed in their motors and they are used when high maneuverability is required, since they are capable of moving in any direction or flying at low speeds. Due to the complexity of the system, different algorithms have been developed to achieve autonomous control in Unmanned Aerial Vehicles, using techniques from linear control methodologies with PID [10,11], to nonlinear control techniques 2 of 24 such as Feedback Linearization control, model predictive control, adaptive control approaches [12], fail-safe methodologies based on sliding mode control theory and backstepping control [13,14], combinations such as Adaptive Sliding Backstepping Control [15][16][17], diffuse control in the proposal of Geometric Control [18,19], Nonlinear Dynamic In-version (NDI) Control [20], the Robust Generalized Dynamic Inversion (RGDI) Quadcopter Control System [21] and the Neural Network Control System of UAV Altitude Dynamics [22][23][24][25]; most of these state-of-the-art nonlinear and adaptive control techniques for quadrotors were discussed by Hongwei and Ghulam.…”
Section: Introductionmentioning
confidence: 99%
“…However, the complex dynamic characteristics and the signal characteristics of high-amplitude interference are not analyzed. Aiming at the problem of parameter adjustment, Gao et al 12 proposed a tracking differentiator that can adjust parameters adaptively. The frequency information is used to realize the trade-off between noise suppression and phase lag, which improves the High-frequency signal tracking ability.…”
Section: Introductionmentioning
confidence: 99%